A Critical Discourse Analysis of song “Look What You Made Me Do” by Taylor Swift - Alek Alek; Abdul Gafur Marzuki; Didin Nuruddin Hidayat; Evi Nurisra Aprilia Sari (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
The aim of this study was to reveal on how the intended meaning of any figurative expressions delivered through the lyrics and also symbolic signs and gestures which delivered on a popular video clip of Taylor Swift “Look What You Made Me Do” in order to figure out its implication toward language learning as one of the most-watched music videos on YouTube. The data of this study were the lyrics of Taylor Swift’s song “Look What You Made Me Do” and the official video clip on YouTube uploaded by VIVO on August 27th, 2017. Both the lyrics and the symbolic cues shown on the video clip were analyzed through Fairclough’s critical discourse analysis by categorizing any kinds of figurative expressions delivered to reveal the intended meaning of the song and interpret its symbolic expressions through semiotic study as research method. Thus the context is intervening the writing of the song. The results showed that there are many repetitions found to emphasize the message delivered which can be considered as something that viewed as highly really matter for the author or the singer of the song then based on the symbolic or semiotic analysis, most of the clues delivered are trying to express the singers’ transformation regarding to her new reputation as a more powerful and tough person from her past image as an innocent sweet girl. The clues are delivered through the symbols in the forms of animals such as snakes and raven which belief as the symbols of transformation.